Expression and membrane integration of SARS-CoV E protein and its interaction with M protein - Chen, Shih-Chi (Virus Genes, 2009)
The severe acute respiratory syndrome (SARS)-CoV E gene fragment was cloned and expressed as a recombinant protein fused with a myc tag at the N-terminus in vitro and in Vero E6 cells. Similar to other N-glycosylated proteins, the glycosylation of SARS-CoV E protein occurred co-translationally in the presence of microsomes. The SARS-CoV E protein is predicted to be a double-spanning membrane protein lacking a conventional signal peptide. Both of the transmembrane regions (a.a. 11–33 and 37–59) are predicted to be α-helices, which penetrate into membranes by themselves. As expected, these two transmembrane regions inserted a cytoplasmic protein into the endoplasmic reticulum membrane. Either of these two transmembrane domains co-localized with M protein. Both the transmembrane domains of E protein are required to interact with M protein, while either of the hydrophilic regions (a.a. 1–10 or 60–76) is dispensable as shown by co-immunoprecipitation assay. These results are important for the study of SARS-CoV assembly. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11262-009-0341-6) contains supplementary material, which is available to authorized users.